Event program : "Heydar Aliyev Centennial Book Fair : Celebrating a Century of Dedication, Leadership, and Inspiration" - ADA University Library (ADA University, 2023)
Event program for the International Book, Science and Culture holiday dedicated to the 100th anniversary of National Leader Heydar Aliyev.
Keywords: ADA University -- Book fair.; ADA University -- Book fair -- Program.; ADA University -- Aliyev, Heydar -- Centennial.